Simmel: A Ruína - Carlos Fortuna (Olhares, 2019)
It presents the centenary essay of Simmel The Ruin, in a version of 1919 although the text originally appeared in 1911, and discusses the author's approach to aesthetics and the meaning of classical ruin. At the same time, the (post)industrial ruins are disallowed, which allows questions about the current hypotheses of the German philosopher. The ruin of Simmel argues about the conflict of nature with the spirit and the way the "revolt" of nature that generates the ruin, also produces peace and temperance. The treatment of Simmel presents general traces of the romantic assessment of ruin and is not immediate its approximation to the context of contemporary ruin resulting from human action (Incuria, degradation and wars). It is this industrial (post) ruin that is brought to the comparison and that by marking two consecrated cases of contemporary urban ruin - Aleppo and Detroit - makes highlighting the aesthetic order of decay in which the contrast with the ruin of Simmel gains sense and actuality.